PREVALENCE OF BURNOUT AND DEPRESSIVE SYMPTOMS AMONG HEALTHCARE WORKERS IN THE CORONAVIRUS DISEASE 2019 PANDEMIC IN BELGRADE - Giljača, Sonja; Giljača, Sonja (Acta medicae Medianae, 2025)
A cross-sectional study was conducted among all the employees of the “Barajevo” Health Center using the following questionnaires: Maslach Burnout Inventory-Human Services Survey (MBI-HSS) for measuring three aspects of the burnout syndrome (emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA)); Patient Health Quality 9 (PHQ-9) for self-assessment of depressive symptoms, and sociodemographic characteristics of respondents were collected through a general questionnaire. Only completely completed questionnaires were included in the study, which was 71. No statistically significant differences were found between the frequency of depressive symptoms based on the score of the PHQ9 questionnaire among both medical and non-medical personnel as well as among employees in the COVID-19 and non-COVID 19 zones. Based on the average values of the scores of the PHQ9 questionnaire, it was determined that the employees who worked in the COVID-19 zone had a significantly higher (p < 0.05) average value of the PHQ9 score (6.84 ± 5.73) compared to the average value of the PHQ9 score of employees in the non-COVID-19 zone (4.00 ± 3.70). A moderate to high level of emotional exhaustion was observed in more than 50% of respondents. Low level of depersonalization was noted in 70.4%, whereas the majority of employees, 53.5%, exhibited low levels of personal accomplishment. Only 1 patient (1.4%) met all three criteria for high burnout, while 67 (94.4%) of them belonged to the moderate overall burnout category.
Keywords: burnout syndrome, coronavirus disease 2019, healthcare workers, symptoms of depression